PENGARUH METODE PQ4R TERHADAP MOTIVASI DAN HASIL PERKULIAHAN BAHASA INDONESIA MAHASISWA UNIVERSITAS SYEDZA SAINTIKA - Fitra Afrida Amna; Elvina A Saibi (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the effect of the application of the PQ4R (Preview, Question, Read, Reflect, Recite, Review) method on students' learning motivation and lecture outcomes in the Indonesian Language course. The PQ4R method is a learning strategy that combines various stages of information processing with the aim of improving understanding and retention of the material studied. This study uses a quantitative approach with a quasi-experimental design, involving two groups of students: the experimental group that receives treatment using the PQ4R method and the control group that uses the conventional method. The sample of this study consisted of 60 students, who were randomly selected from the first-semester student population at a university. Data collection was carried out through questionnaires to measure learning motivation and learning outcome tests developed by researchers. Data analysis was carried out using statistical analysis techniques, namely t-tests to compare motivation and learning outcomes between the two groups. The results showed that there was a significant difference between the experimental group and the control group in terms of learning motivation and learning outcomes. The group of students who used the PQ4R method showed a higher increase in learning motivation compared to the control group. In addition, the results of the experimental group lectures were also significantly better than the control group, which indicates the effectiveness of the PQ4R method in improving the understanding and retention of lecture materials. The conclusion of this study is that the PQ4R method has a positive influence on student motivation and learning outcomes in Indonesian Language courses. The implications of this study show that the application of the PQ4R method can be an effective alternative learning strategy to improve the quality of learning in higher education, especially in courses that require in-depth understanding and high material retention. Further research is suggested to explore the application of this method to other courses and with a more diverse population.